2016
DOI: 10.7717/peerj.1748
|View full text |Cite
|
Sign up to set email alerts
|

The (mis)measurement of the Dark Triad Dirty Dozen: exploitation at the core of the scale

Abstract: Background. The dark side of human character has been conceptualized in the Dark Triad Model: Machiavellianism, psychopathy, and narcissism. These three dark traits are often measured using single long instruments for each one of the traits. Nevertheless, there is a necessity of short and valid personality measures in psychological research. As an independent research group, we replicated the factor structure, convergent validity and item response for one of the most recent and widely used short measures to op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 52 publications
5
55
0
4
Order By: Relevance
“…As such, malevolent character expresses the characteristics of multi-finality and equifinality. That being said, previous studies suggest that the dark triad is rather a dyad, with an antisocial and manipulative factor and a narcissistic factor (e.g., , Kajonius, Persson, Garcia, & Rosenberg, 2016. Others have also pointed out that darkness is just the absence of light, and that we probably need to investigate the lack or underdevelopment of light character traits in order to understand what makes societies flourish or perish cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, malevolent character expresses the characteristics of multi-finality and equifinality. That being said, previous studies suggest that the dark triad is rather a dyad, with an antisocial and manipulative factor and a narcissistic factor (e.g., , Kajonius, Persson, Garcia, & Rosenberg, 2016. Others have also pointed out that darkness is just the absence of light, and that we probably need to investigate the lack or underdevelopment of light character traits in order to understand what makes societies flourish or perish cf.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals high in Machiavellianism are manipulative (Jones & Paulhus, 2009), have a cynical worldview and lack morality (Christie & Geis, 1970), individuals high in narcissism have a tremendous sense of grandiosity and need for exhibitionism but, at the same time, a vulnerable self-esteem (Morf & Rhodewalt, 2001;Raskin R & Hall, 1979), and individuals high in psychopathy are low in empathy, low in conscientiousness, experience low levels of anxiety, are highly impulsive, and express high levels of thrill-seeking behavior (Furnham, Richards, & Paulhus, 2013, Hare, 1985. Hence, individuals high in any of the dark character traits have one core behavior in common: uncooperativeness (Garcia, Adrianson, Archer, & Rosenberg, 2015;Kajonius, Persson, Rosenberg, & Garcia, 2016). In other words, individuals who express these malevolent character traits or the lack of a mature character (i.e., low empathy, low self-control, and low "moral intuition") might orient society towards violence (i.e., separation) and away from cooperation and altruism (i.e., unity) (cf.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they used Dirty Dozen (Jonason & Webster, 2010), which has been considered too brief to capture critical construct variance (Maples, Lamkin, & Miller, 2014). Consequently, studies suggest that it is better conceptualized as a combined Machiavellianism-psychopathy factor than threefactor scale (e.g., Kajonius, Persson, Rosenberg, & Garcia, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the Dark Triad traits reflect a meaningful and evolutionary relevant latent construct (Jonason et al, 2009), and idea that has received support from overseas researchers (Bertl, Pietschnig, Tran, Stieger, & Voracek, 2017) and those parsing the shared and unique variance using structural equation modelling in relation to important outcomes like sexual assault (Figueredo et al, 2015;Jonason, Girgis, & Milne-Home, 2017). However, recent evidence has also claimed there might not even be three traits but, merely a combined Machiavellianism and psychopathy factor with narcissism standing alone for both the SD3 and the DD measures (Kajonius, Persson, Rosenberg, & Garcia, 2016;Persson, Kajonius, & Garcia, 2017). Others still suggest that the Dark Triad consists primarily of psychopathy (Glenn & Sellbom, 2015); a contention that is often verified when the outcome the Dark Triad traits are indexed on is 'dark' itself (James et al, 2014).…”
mentioning
confidence: 99%